Answer: To complete the recursive formula for g(n) = -50 - 15n, we need to find an expression for g(n) in terms of previous terms of the sequence.
One way to do this is to notice that g(n) can be obtained by subtracting 15 from the previous term, g(n-1):
g(n) = -50 - 15n
= -50 - 15(n-1) - 15 (adding and subtracting 15)
= g(n-1) - 15
Therefore, the recursive formula for g(n) is:
g(0) = -50 (base case)
g(n) = g(n-1) - 15 (recursive step)
This means that to find g(n), we need to first find g(n-1) and then subtract 15 from it. We can use this recursive formula to generate any term in the sequence of g(n).
Explanation: